Beta-1 and Beta-2 adrenergic receptor polymorphism and association with cardiovascular response to orthostatic screening - Wittwer, ED (2011)
Variation in the beta-1 and beta-2 adrenergic receptor genes (ADRB1 and ADRB2, resp.) may influence cardiovascular reactivity including orthostatic stress. We tested this hypothesis in a head-up tilt (HUT) screening protocol in healthy young adults without history of syncope. Following brachial arterial catheter insertion, 120 subjects (age 18–40, 72 females, Caucasian) underwent 5 min 60° HUT. Polymorphisms tested were: Ser49/Gly and Arg389/Gly in ADRB1; Arg16/Gly, Gln27/Glu, and Thr164/Ile in ADRB2. Three statistical models (recessive, dominant, additive) were evaluated using general linear models with analysis for each physiologic variable. A recessive model demonstrated a significant association between Arg16/Gly and: absolute supine and upright HR; HUT-induced change in cardiac index (CI), stroke index (SI) and systemic vascular resistance (SVR); and supine and upright norepinephrine values. Blood pressure was not influenced by genotype. Fewer associations were present for other polymorphisms: Ser49/Gly and the change in SI (dominant model), and Arg389/Gly and supine and HUT norepinephrine (additive model). We conclude that in this population, there is a robust association between Arg16/Gly and HUT responses, such that 2 copies of Arg16 increases supine and upright HR, and greater HUT-induced decreases in CI and SI, with greater increases in SVR and norepinephrine. ADRB1 gene variation appears to impact SI and plasma NE levels but not HR. Whether ADRB2 gene variation is ultimately disease-causing or disease-modifying, this study suggests an association between Arg16/Gly and postural hemodynamics, with sympathetic noradrenergic activity affected in a similar direction. This may have implications in the development of orthostatic disorders.